Post-translational Regulation of Adipose Differentiation-related Protein by the Ubiquitin/Proteasome Pathway - Guoheng Xu; Carole Sztalryd; Xinyue Lu; John T. Tansey; Jai-Wei Gan; Heidi Dorward; Alan R. Kimmel; Constantine Londos (2005)
Adipose differentiation-related protein (ADRP) is localized to lipid droplets in most mammalian cells. ADRP, proposed to regulate fatty acid mobilization and lipid droplet formation, is linked to lipid accumulation in foam cells of human atherosclerotic lesions. In this report, we show that ADRP protein accumulates in Chinese hamster ovary fibroblastic cells cultured in the presence of oleic acid but is destabilized when fatty acid sources are removed from culture serum. The latter effect was blocked by the proteasome inhibitor MG132, whereas inhibitors of other proteolytic processes were ineffective. Pulse-chase experiments confirmed that ADRP degradation is inhibited by MG132. Conditions that stimulate ADRP degradation also promoted the covalent modification of ADRP by ubiquitin, whereas the addition of oleic acid to culture media, which promotes triacylglycerol deposition, blunted the appearance of ubiquitinated-ADRP. Treatment with MG132 increased the levels of ADRP associated with lipid droplets, as well as throughout the cytosol. Finally, we demonstrate that the disappearance of ADRP protein after the onset of perilipin expression during adipocyte differentiation is due to degradation by proteasomes Thus, proteolytic degradation of ADRP mediated through the ubiquitin/proteasome pathway appears to be a major mode for the post-translational regulation of ADRP. Adipose differentiation-related protein (ADRP) is localized to lipid droplets in most mammalian cells. ADRP, proposed to regulate fatty acid mobilization and lipid droplet formation, is linked to lipid accumulation in foam cells of human atherosclerotic lesions. In this report, we show that ADRP protein accumulates in Chinese hamster ovary fibroblastic cells cultured in the presence of oleic acid but is destabilized when fatty acid sources are removed from culture serum. The latter effect was blocked by the proteasome inhibitor MG132, whereas inhibitors of other proteolytic processes were ineffective. Pulse-chase experiments confirmed that ADRP degradation is inhibited by MG132. Conditions that stimulate ADRP degradation also promoted the covalent modification of ADRP by ubiquitin, whereas the addition of oleic acid to culture media, which promotes triacylglycerol deposition, blunted the appearance of ubiquitinated-ADRP. Treatment with MG132 increased the levels of ADRP associated with lipid droplets, as well as throughout the cytosol. Finally, we demonstrate that the disappearance of ADRP protein after the onset of perilipin expression during adipocyte differentiation is due to degradation by proteasomes Thus, proteolytic degradation of ADRP mediated through the ubiquitin/proteasome pathway appears to be a major mode for the post-translational regulation of ADRP. Intracellular neutral lipid storage droplets in eukaryotes are ubiquitous cellular organelles required for membrane biosynthesis, cholesterol metabolism, and energy balance (1Murphy D.J. Vance J. Trends. Biochem. Sci. 1999; 24: 109-115Abstract Full Text Full Text PDF PubMed Scopus (482) Google Scholar, 2Zweytick D. Athenstaedt K. Daum G. Biochim. Biophys. Acta. 2000; 1469: 101-120Crossref PubMed Scopus (271) Google Scholar). Lipid droplets contain a triacylglycerol (TAG) 6The abbreviations used are: TAGtriacylglycerolADRPadipose differentiation-related proteinALLNN-acetyl-l-leucyl-l-leucyl-l-norleucinalCHOChinese hamster ovaryDMEMDulbecco's modified Eagle's mediumFCSfetal calf serumPBSphosphate-buffered salineOAoleic acidAdadenovirus. and cholesterol ester core surrounded by a phospholipid monolayer (3Brown D.A. Curr. Biol. 2001; 11: R446-R449Abstract Full Text Full Text PDF PubMed Scopus (222) Google Scholar). Several related proteins localize to the surface of lipid droplets (4Londos C. Brasaemle D.L. Schultz C.J. Segrest J.P. Kimmel A.R. Semin. Cell Dev. Biol. 1999; 10: 51-58Crossref PubMed Scopus (368) Google Scholar), including perilipin (5Greenberg A.S. Egan J.J. Wek S.A. Moos Jr., M.C. Londos C. Kimmel A.R. Proc. Natl. Acad. Sci. U. S. A. 1993; 90: 12035-12039Crossref PubMed Scopus (211) Google Scholar, 6Servetnick D.A. Brasaemle D.L. Gruia-Gray J. Kimmel A.R. Wolff J. Londos C. J. Biol. Chem. 1995; 270: 16970-16973Abstract Full Text Full Text PDF PubMed Scopus (164) Google Scholar, 7Blanchette-Mackie E.J. Dwyer N.K. Barber T. Coxey R.A. Takeda T. Rondinone C.M. Theodorakis J.L. Greenberg A.S. Londos C. J. Lipid Res. 1995; 36: 1211-1226Abstract Full Text PDF PubMed Google Scholar, 8Brasaemle D.L. Barber T. Kimmel A.R. Londos C. J. Biol. Chem. 1997; 272: 9378-9387Abstract Full Text Full Text PDF PubMed Scopus (129) Google Scholar), adipose differentiation-related protein (ADRP) (9Brasaemle D.L. Barber T. Wolins N.E. Serrero G. Blanchette-Mackie E.J. Londos C. J. Lipid Res. 1997; 38: 2249-2263Abstract Full Text PDF PubMed Google Scholar), TIP47 (10Wolins N.E. Rubin B. Brasaemle D.L. J. Biol. Chem. 2001; 276: 5101-5108Abstract Full Text Full Text PDF PubMed Scopus (245) Google Scholar, 11Miura S. Gan J.W. Brzostowski J. Parisi M.J. Schultz C.J. Londos C. Oliver B. Kimmel A.R. J. Biol. Chem. 2002; 277: 32253-32257Abstract Full Text Full Text PDF PubMed Scopus (307) Google Scholar), a putative cargo protein for the mannose 6-phosphate receptors (12Diaz E. Pfeffer S.R. Cell. 1998; 93: 433-443Abstract Full Text Full Text PDF PubMed Scopus (327) Google Scholar), and S3–12 (13Wolins N.E. Skinner J.R. Schoenfish M.J. Tzekov A. Bensch K.G. Bickel P.E. J. Biol. Chem. 2003; 278: 37713-37721Abstract Full Text Full Text PDF PubMed Scopus (171) Google Scholar). These proteins share sequence homology within their PAT (perilipin/ADRP/TIP47) domains (4Londos C. Brasaemle D.L. Schultz C.J. Segrest J.P. Kimmel A.R. Semin. Cell Dev. Biol. 1999; 10: 51-58Crossref PubMed Scopus (368) Google Scholar, 11Miura S. Gan J.W. Brzostowski J. Parisi M.J. Schultz C.J. Londos C. Oliver B. Kimmel A.R. J. Biol. Chem. 2002; 277: 32253-32257Abstract Full Text Full Text PDF PubMed Scopus (307) Google Scholar, 14Hickenbottom S.J. Kimmel A.R. Londos C. Hurley J.H. Structure (Camb.). 2004; 12: 1199-1207Abstract Full Text Full Text PDF PubMed Scopus (155) Google Scholar) and are derived from a common ancestral gene (15Lu X. Gruia-Gray J. Copeland N.G. Gilbert D.J. Jenkins N.A. Londos C. Kimmel A.R. Mamm. Genome. 2001; 12: 741-749Crossref PubMed Scopus (183) Google Scholar). triacylglycerol adipose differentiation-related protein N-acetyl-l-leucyl-l-leucyl-l-norleucinal Chinese hamster ovary Dulbecco's modified Eagle's medium fetal calf serum phosphate-buffered saline oleic acid adenovirus. The localization to lipid droplets suggests that PAT proteins play a fundamental role in lipid metabolism (4Londos C. Brasaemle D.L. Schultz C.J. Segrest J.P. Kimmel A.R. Semin. Cell Dev. Biol. 1999; 10: 51-58Crossref PubMed Scopus (368) Google Scholar, 16Londos C. Brasaemle D.L. Schultz C.J. Adler-Wailes D.C. Levin D.M. Kimmel A.R. Rondinone C.M. Ann. N. Y. Acad. Sci. 1999; 892: 155-168Crossref PubMed Scopus (221) Google Scholar). To date, perilipin is the only family member for which a function in lipid metabolism has been firmly established (17Sztalryd C. Xu G. Dorward H. Tansey J.T. Contreras J.A. Kimmel A.R. Londos C. J. Cell Biol. 2003; 161: 1093-1103Crossref PubMed Scopus (422) Google Scholar), for review see Tansey et al. (18Tansey J.T. Sztalryd C. Hlavin E.M. Kimmel A.R. Londos C. IUBMB Life. 2004; 56: 379-385Crossref PubMed Scopus (195) Google Scholar). Lipolysis in adipocytes is governed primarily by a protein kinase A-mediated reaction. Non-protein kinase A-phosphorylated perilipin protects TAG from hydrolysis and thus promotes TAG storage (19Brasaemle D.L. Rubin B. Harten I.A. Gruia-Gray J. Kimmel A.R. Londos C. J. Biol. Chem. 2000; 275: 38486-38493Abstract Full Text Full Text PDF PubMed Scopus (369) Google Scholar, 20Tansey J.T. Huml A.M. Vogt R. Davis K.E. Jones J.M. Fraser K.A. Brasaemle D.L. Kimmel A.R. Londos C. J. Biol. Chem. 2003; 278: 8401-8406Abstract Full Text Full Text PDF PubMed Scopus (177) Google Scholar). Indeed perilipin-null mice have reduced adipose TAG storage (21Tansey J.T. Sztalryd C. Gruia-Gray J. Roush D.L. Zee J.V. Gavrilova O. Reitman M.L. Deng C.X. Li C. Kimmel A.R. Londos C. Proc. Natl. Acad. Sci. U. S. A. 2001; 98: 6494-6499Crossref PubMed Scopus (609) Google Scholar, 22Martinez-Botas J. Anderson J.B. Tessier D. Lapillone A. Chang B. H.-J. Quast M.J. Forenstein D. Chen K.H. Chan L. Nat. Genet. 2000; 26: 474-479Crossref PubMed Scopus (495) Google Scholar). However phosphorylation of perilipin is required for the translocation of hormone-sensitive lipase from the cytosol to the lipid droplet surface (17Sztalryd C. Xu G. Dorward H. Tansey J.T. Contreras J.A. Kimmel A.R. Londos C. J. Cell Biol. 2003; 161: 1093-1103Crossref PubMed Scopus (422) Google Scholar). Because migration of hormone-sensitive lipase largely determines lipolytic activation in adipocytes, stimulation of lipolysis is strongly blunted in isolated primary adipocytes that lack perilipin or in whole perilipin-null animals (21Tansey J.T. Sztalryd C. Gruia-Gray J. Roush D.L. Zee J.V. Gavrilova O. Reitman M.L. Deng C.X. Li C. Kimmel A.R. Londos C. Proc. Natl. Acad. Sci. U. S. A. 2001; 98: 6494-6499Crossref PubMed Scopus (609) Google Scholar). ADRP, also termed adipophilin, is a 47-kDa protein that shares sequence similarity with perilipin (4Londos C. Brasaemle D.L. Schultz C.J. Segrest J.P. Kimmel A.R. Semin. Cell Dev. Biol. 1999; 10: 51-58Crossref PubMed Scopus (368) Google Scholar). Unlike perilipin which is specific for adipocytes and steroidogenic cells (5Greenberg A.S. Egan J.J. Wek S.A. Moos Jr., M.C. Londos C. Kimmel A.R. Proc. Natl. Acad. Sci. U. S. A. 1993; 90: 12035-12039Crossref PubMed Scopus (211) Google Scholar, 6Servetnick D.A. Brasaemle D.L. Gruia-Gray J. Kimmel A.R. Wolff J. Londos C. J. Biol. Chem. 1995; 270: 16970-16973Abstract Full Text Full Text PDF PubMed Scopus (164) Google Scholar, 7Blanchette-Mackie E.J. Dwyer N.K. Barber T. Coxey R.A. Takeda T. Rondinone C.M. Theodorakis J.L. Greenberg A.S. Londos C. J. Lipid Res. 1995; 36: 1211-1226Abstract Full Text PDF PubMed Google Scholar), ADRP is expressed in most tissues (9Brasaemle D.L. Barber T. Wolins N.E. Serrero G. Blanchette-Mackie E.J. Londos C. J. Lipid Res. 1997; 38: 2249-2263Abstract Full Text PDF PubMed Google Scholar, 23Heid H.W. Moll R. Schwetlick I. Rackwitz H.R. Keenan T.W. Cell Tissue Res. 1998; 294: 309-321Crossref PubMed Scopus (362) Google Scholar, 24Steiner S. Wahl D. Mangold B.L.K Robison R. Raymackers J. Meheus L. Anderson N.L. Cordier A. Biochem. Biophys. Res. Commun. 1996; 218: 777-782Crossref PubMed Scopus (63) Google Scholar). ADRP is suggested to selectively increase the uptake of long chain fatty acids and has a possible role in fatty acid transport (25Serrero G. Frolov A. Schroeder F. Tanaka K. Gelhaar L. Biochim. Biophys. Acta. 2000; 1488: 245-254Crossref PubMed Scopus (40) Google Scholar, 26Gao J. Serrero G. J. Biol. Chem. 1999; 274: 16825-16830Abstract Full Text Full Text PDF PubMed Scopus (195) Google Scholar, 27Gao J. Ye H. Serrero G. J. Cell. Physiol. 2000; 182: 297-302Crossref PubMed Scopus (97) Google Scholar). Cells cultured with fatty acids may have elevated ADRP mRNA and protein expression (26Gao J. Serrero G. J. Biol. Chem. 1999; 274: 16825-16830Abstract Full Text Full Text PDF PubMed Scopus (195) Google Scholar, 27Gao J. Ye H. Serrero G. J. Cell. Physiol. 2000; 182: 297-302Crossref PubMed Scopus (97) Google Scholar). In lung tissue, the developmental expression pattern of ADRP mRNA and protein parallel TAG accumulation (28Schultz C.J. Torres E. Londos C. Torday J.S. Am. J. Physiol. 2002; 283: L288-L296Crossref PubMed Scopus (104) Google Scholar). ADRP not only serves as a sensitive marker of lipid accumulation (23Heid H.W. Moll R. Schwetlick I. Rackwitz H.R. Keenan T.W. Cell Tissue Res. 1998; 294: 309-321Crossref PubMed Scopus (362) Google Scholar, 29Buechler C. Ritter M. Duong C.Q. Orso E. Kapinsky M. Schmitz G. Biochim. Biophys. Acta. 2001; 1532: 97-104Crossref PubMed Scopus (82) Google Scholar) but also has been reported to stimulate lipid accumulation and lipid droplet formation in murine fibroblasts (30Imamura M. Inoguchi T. Ikuyama S. Taniguchi S. Kobayashi K. Nakashima N. Nawata H. Am. J. Physiol. 2002; 283: E775-E783Crossref PubMed Scopus (236) Google Scholar). A recent study has revealed that ADRP mRNA is induced in human monocytes or macrophages by either oxidized (31Wang X. Reape T.J. Li X. Rayner K. Webb C.L. Burnand K.G. Lysko P.G. FEBS Lett. 1999; 462: 145-150Crossref PubMed Scopus (88) Google Scholar) or enzymatically modified (29Buechler C. Ritter M. Duong C.Q. Orso E. Kapinsky M. Schmitz G. Biochim. Biophys. Acta. 2001; 1532: 97-104Crossref PubMed Scopus (82) Google Scholar) low density lipoprotein and is highly expressed in a subset of lipid-rich foam cells of human atherosclerotic lesions (31Wang X. Reape T.J. Li X. Rayner K. Webb C.L. Burnand K.G. Lysko P.G. FEBS Lett. 1999; 462: 145-150Crossref PubMed Scopus (88) Google Scholar). By contrast, perilipin mRNA is induced in foam cells of ruptured, but not of stable, human atherosclerotic plaques (32Faber B.C. Cleutjens K.B. Niessen R.L. Aarts P.L. Boon W. Greenberg A.S. Kitslaar P.J. Tordoir J.H. Daemen M.J. Circ. Res. 2001; 89: 547-554Crossref PubMed Scopus (119) Google Scholar). Thus, the lipid droplet-associated proteins such as ADRP and perilipin are likely potential regulators for lipid accumulation of foam cells and destabilization of atherosclerotic plaque. Although the PAT family proteins appear to play important roles in lipid metabolism, there are few studies on the regulation of these proteins; most available evidence points toward a post-translational regulation of ADRP. The ubiquitin/proteasome pathway is a potential mechanism for such regulation. Ubiquitin is an 8-kDa peptide of 76 amino acids that is ubiquitous in eukaryotes. Typically, ubiquitin or a polyubiquitin chain is covalently conjugated with the targeted protein to form polyubiquitinated protein complexes, which are delivered to and degraded by the 26 S proteasome, a 2000-kDa ATP-dependent proteolytic particle (33Ciechanover A. Schwartz A.L. Proc. Natl. Acad. Sci. U. S. A. 1998; 95: 2727-2730Crossref PubMed Scopus (348) Google Scholar, 34Wilkinson K.D. J. Nutr. 1999; 129: 1933-1936Crossref PubMed Scopus (63) Google Scholar, 35Wilkinson K.D. Semin. Cell Dev. Biol. 2000; 11: 141-148Crossref PubMed Scopus (468) Google Scholar). If proteins fold improperly or form incorrect oligomeric structures, they may become conjugated to ubiquitin and proteasomally degraded (33Ciechanover A. Schwartz A.L. Proc. Natl. Acad. Sci. U. S. A. 1998; 95: 2727-2730Crossref PubMed Scopus (348) Google Scholar, 35Wilkinson K.D. Semin. Cell Dev. Biol. 2000; 11: 141-148Crossref PubMed Scopus (468) Google Scholar). In the cellular response to environmental changes, the ubiquitin/proteasome system has been shown to regulate degradation of transcription factors, cell cycle proteins, tumor suppressors, and cell surface receptors, as well as proteins that are damaged or improperly localized (34Wilkinson K.D. J. Nutr. 1999; 129: 1933-1936Crossref PubMed Scopus (63) Google Scholar). In this study, we report that a major mode for the post-translational regulation of ADRP is degradation via the ubiquitin/proteasome pathway. Reagents—Unless otherwise noted, all chemical reagents were obtained from Sigma. Proteasome or protease inhibitors MG132, lactacystin, ALLN, calpeptin, and leupeptin were purchased from Calbiochem. Geneticin (G418) and DNA transfection reagents came from Invitrogen. [35S]Methionine and an enhanced chemiluminescence (ECL) detection kit were products of Amersham Biosciences. Methionine-free DMEM is a product of BioFluids (Rockville, MD). Rabbit and goat anti-mouse ADRP polyclonal sera were raised against a peptide composed of the N-terminal 26 amino acid residues of murine ADRP. Rabbit anti-ubiquitin antibody, agarose-conjugated protein A/G plus mixture, and horseradish peroxidase-conjugated IgG were obtained from Santa Cruz Biotechnology. Fluorescein isothiocyanate-conjugated donkey anti-rabbit IgG were purchased from Jackson Immunoresearch. Cells Culture and Expression of ADRP in CHO Cells—Chinese hamster ovary fibroblastic cells (CHO-K1, ATTC) were maintained in F12 medium (Invitrogen) containing 10% fetal calf serum (FCS), 100 units/ml penicillin, and 100 units/ml streptomycin at 37 °C in an atmosphere of 5% CO2. Full-length mouse ADRP cDNA was subcloned in the pcDNA3.1 vector and transfected into CHO cells using the Lipofectamine Plus reagent (Invitrogen). After selection in 1500 μg/ml G418 (Invitrogen) for four generations, cells that stably expressed ADRP (CHO-ADRP) were maintained in 10% FCS-F12 medium in the presence of 300 μg/ml G418. For transient ADRP expression, CHO cells were infected with a recombinant adenovirus-expressing murine ADRP (Ad-ADRP). This vector was constructed according to a previously described method (17Sztalryd C. Xu G. Dorward H. Tansey J.T. Contreras J.A. Kimmel A.R. Londos C. J. Cell Biol. 2003; 161: 1093-1103Crossref PubMed Scopus (422) Google Scholar). For lipid loading, oleic acid was added to the culture medium at 400 μmol as a 5:1 molar complex with bovine serum albumin. For delipidation experiments, cells were cultured in medium containing 10% charcoal-delipidated FCS (Sigma). Immunoblot Analysis—Cells were washed twice, lysed in sample buffer, diluted 1:1 with 2× SDS loading buffer, and heated to ∼95 °C for 5 min. Equivalent amounts of protein were loaded, separated by 10% SDS-PAGE, and transferred to nitrocellulose membranes. The membrane was blocked using 5% nonfat dry milk in TBS buffer containing 150 mm NaCl, 0.05% Tween 20, and 20 mm Tris-HCl, pH 7.2, and incubated for 1 h with primary antibodies against ADRP followed by incubation for 1 h with specific secondary antibodies conjugated to horseradish peroxidase. Blots were developed using an enhanced chemiluminescence (ECL) detection kit. Northern Blot Analysis—CHO cells were grown to 80% confluence, and total cellular RNA was extracted using TRIzol reagent (Invitrogen). Thirty μg of total RNA was loaded in each lane, separated in 1% formaldehyde denaturing agarose gel, and transferred to nylon membranes. 32P-Labeled ADRP cDNA probe was prepared with the Rediprime DNA random labeling system (Amersham Biosciences), and unincorporated nucleotides were removed through a G-50 desalting spin column. The membrane was baked for 2 h at 80°C prior to prehybridization. The hybridization procedures were performed in the presence of 32P-labeled ADRP cDNA probe in Ultrahyb solution (Ambion) at 42 °C. ADRP mRNA bands were detected by autoradiography. Immunoprecipitation—Cells grown in 60-mm diameter dishes were washed twice with PBS buffer and lysed in 1 ml of cold RIPA lysis buffer (50 mm Tris-HCl, pH 7.5, 150 mm NaCl, 1% Nonidet P-40, 0.5% sodium deoxycholate, 0.1% SDS, and 2 mm EDTA) with proteases inhibitors (2 mm phenylmethylsulfonyl fluoride, 2 μg/ml ALLN, 2 μg/ml leupeptin, and 2 μg/ml aprotinin). After addition of the lysis buffer, the dishes were incubated on ice for 20 min. The cell lysates were centrifuged at 13,000 rpm at 4 °C for 20 min to pellet cell debris. The supernatant was transferred to a new tube and precleared with 30 μl of agarose-protein A/G plus mixture for 1 h at 4 °C. The immunoprecipitation reaction was performed at 4 °C for 2 h on a rotator in 1 ml of the precleared supernatant upon addition of rabbit anti-ADRP antibody at 1:500 or rabbit anti-ubiquitin at 1:200 and 30 μl of agarose-protein A/G plus mixture. Rabbit polyclonal serum against hormone-sensitive lipase or rabbit preimmune serum was used as the negative control. The immunoprecipitated complex was pelleted by centrifugation at 5000 rpm at 4 °C for 5 min, washed four times with cold RIPA buffer, and finally mixed with sample buffer containing 4% SDS and 10 mm dithiothreitol. After boiling at 100 °C for 5 min, proteins in the samples were loaded and separated by SDS-PAGE. For pulse-chase experiments, [35S]methionine-labeled ADRP in immunoprecipitates was detected directly by autoradiography after separation by SDS-PAGE and exposure of the dried gel to X-film for 24 h. For subsequent immunoblot analysis, the immunoprecipitated proteins were separated on SDS-PAGE and transferred to nitrocellulose membrane followed by immunoblotting with the antibodies against ADRP or ubiquitin, respectively. Pulse-Chase Experiments—Cells were grown to 90% confluence in 60-mm diameter dishes and preincubated for 30 min in methionine-free 10% FCS-DMEM to deplete cold methionine from the cells. The cells were washed once with PBS and then pulse-labeled for 5 h with 0.1 mCi/ml [35S]methionine in warmed methionine-free DMEM-10% FCS. Pulse-labeling reaction was terminated by the addition of a 1,000-fold excess of cold methionine. After one wash with PBS, cells were subsequently chased for 0 or 5 h in serum-free F12 culture medium in the presence or absence of 400 μm oleic acid or 10 μm MG132 as indicated. The [35S]methionine-labeled ADRP reached its maximum level at the end point of labeling and then declined continually during chase. At the end point of the chase, the chase medium was removed, and the cells were washed once with PBS and lysed in 1 ml of cold RIPA buffer. [35S]Methionine-labeled ADRP was immunoprecipitated with rabbit anti-ADRP antibodies and then separated by SDS-PAGE and detected by autoradiography. The density of bands was quantified by densitometry and analyzed using the NIH Image program. Immunofluorescence and Confocal Imaging—Cells were treated in glass slide chambers and fixed for 15 min with 3% paraformaldehyde and 0.1% Triton X-100 in PBS buffer at room temperature followed by three washes for 10 min each with PBS. Nonspecific binding sites in the cells were blocked with 2% donkey serum for 30–60 min and washed for three times for 5 min each. The cells were incubated with rabbit polyclonal serum against ADRP at 1:500 overnight at 4 °C and subsequently with fluorescein isothiocyanate-conjugated donkey anti rabbit IgG at 1:100 for 1 h in the dark at room temperature (17Sztalryd C. Xu G. Dorward H. Tansey J.T. Contreras J.A. Kimmel A.R. Londos C. J. Cell Biol. 2003; 161: 1093-1103Crossref PubMed Scopus (422) Google Scholar). Intracellular lipid storage droplets were easily visible under Nomarski optics/differential interference contrast, and the immunofluorescent signal of ADRP was observed using a Zeiss SCM510 confocal microscope. Quantification of Total Triacyglycerols—Cells grown in 6-well plates were treated with or without 2.5 μm MG132 for 24 h, rinsed with PBS buffer, and scraped into extraction buffer containing 20 mm Tris-HCl, pH 7.4, and 1 mm EDTA. The cells were lysed with three freeze-thaw cycles, and total lipids were extracted with chloroform and methanol (2:1) as described previously (36Folch J. Lees M. Sloane Stanley G.H. J. Biol. Chem. 1957; 226: 497-509Abstract Full Text PDF PubMed Google Scholar). The mass of total triacylglycerols from triplicate samples was measured by OD at 340 nm using a commercial kit (Sigma) and normalized to total cellular protein content measured by the bicinchoninic acid method (Pierce). Differentiation of 3T3-L1 Adipocytes—3T3-L1 (ATCC) fibroblastic cells (preadipocytes) were grown to confluence in 12-well plate and maintained for another 24 h in DMEM containing 10% FCS. The confluent 3T3-L1 cells (day 0) were differentiated for 3 days in 10% FCS-DMEM containing 0.5 mm IBMX (3-isobutyl-1-methyl-xanthine), 10 μm dexamethasone, 1 μg/ml insulin, and 8 μg/ml biotin. The differentiation medium was changed daily, and replaced with regular medium at day 3 after initiating the differentiation program. The differentiated 3T3-L1 adipocytes were maintained in fresh 10% FCS-DMEM. At day 8 of differentiation, the 3T3-L1 adipocytes were treated for 18 h with 5 μm MG132. Statistical Analysis—Data are expressed as the means ± S.E. A oneway analysis of variance Tukey's test was performed for statistical analysis using GraphPad Prism version 4.0, and p values < 0.05 were considered statistically significant. Fatty Acid Loading Promotes Intracellular Lipid Droplet Formation and ADRP Accumulation—We showed previously that CHO cells cultured with the free fatty acid oleic acid (OA) increased TAG storage, with little deposition of OA into other lipid fractions (20Tansey J.T. Huml A.M. Vogt R. Davis K.E. Jones J.M. Fraser K.A. Brasaemle D.L. Kimmel A.R. Londos C. J. Biol. Chem. 2003; 278: 8401-8406Abstract Full Text Full Text PDF PubMed Scopus (177) Google Scholar). To determine whether these growth conditions additionally altered the expression of ADRP, we cultured CHO cells for 48 h in the absence or presence of 400 μm OA and assessed ADRP protein levels by immunofluorescent imaging and confocal microscopy as well as by immunoblotting. Relatively few and tiny lipid droplets (Fig. 1A) were present in CHO cells cultured in the absence of OA. After incubation for 48 h with 400 μm OA, both the number and size of the intracellular lipid storage droplets were significantly increased. We also observed enhanced ADRP immunofluorescence associated with the lipid droplets in cells cultured with OA (Fig. 1A). Increased ADRP protein expression was confirmed by immunoblot analysis (Fig. 1B). Increases in intracellular lipid droplet storage and ADRP accumulation were observed by 12 h after the loading with OA (data not shown). Thus, increases in ADRP protein accumulation paralleled the increase in neutral lipid deposition. Delipidation Induces Down-regulation of ADRP by a Process Blocked by Proteasomal Inhibitors—Delipidation of serum removes lipid precursors and deprives cells of fatty acid precursors that are required for lipid droplet accumulation (9Brasaemle D.L. Barber T. Wolins N.E. Serrero G. Blanchette-Mackie E.J. Londos C. J. Lipid Res. 1997; 38: 2249-2263Abstract Full Text PDF PubMed Google Scholar). Results from Fig. 1 indicate that ADRP protein accumulation was promoted by the increase in intracellular lipid storage. We were interested to determine whether ADRP protein levels would be reduced upon the removal of lipid precursors from the culture media. To enhance ADRP detection, we utilized CHO cells that express ADRP from an adenovirus vector. The linkage of lipid deposition and ADRP expression is highlighted in Fig. 2A. Incubation of the cells for 24 h in culture medium containing 10% calf serum that had been delipidated with charcoal led to a substantial decrease of ADRP protein in comparison with nondelipidated control cells. By contrast, culturing cells in delipidated medium that was supplemented with 400 μm oleic acid prevented the decline in ADRP protein (Fig. 2A). Thus, ADRP appears to be degraded when TAG accumulation is inhibited. To determine whether proteasomal activity is involved in ADRP degradation, we treated the cells with MG132, a specific inhibitor of the 26 S proteasome. Clearly, MG132 promoted ADRP accumulation in cells deprived of lipid precursors (Fig. 2A). Moreover, under nondelipidation conditions, we observed that MG132 elevated ADRP protein in a concentration-dependent manner (Fig. 2B). The MG132-stabilizing effect was evident at 0.625 μm MG132 and maximal at ∼2 μm (Fig. 2B). These results provide strong support that ADRP is degraded through a proteasomal pathway. We investigated the effects of ADRP degradation using a series of protease inhibitors (37Lee D.H. Goldberg A.L. Trends. Cell Biol. 1998; 8: 397-403Abstract Full Text Full Text PDF PubMed Scopus (1252) Google Scholar). It has been well established that MG132 specifically inhibits the 26 S proteasome and that lactacystin is specific for the 20 S proteasome (37Lee D.H. Goldberg A.L. Trends. Cell Biol. 1998; 8: 397-403Abstract Full Text Full Text PDF PubMed Scopus (1252) Google Scholar, 38Mimnaugh E.G. Bonvini P. Neckers L. Electrophoresis. 1999; 20: 418-428Crossref PubMed Scopus (77) Google Scholar). ALLN is an inhibitor of both the 20 S and 26 S proteasomes and a partial inhibitor of the calpain protease. Calpeptin is specific for calpain, leupeptin inhibits trypsin-like and cysteine proteases, and chloroquine and NH4Cl are lysosomal protease inhibitors. As shown in Fig. 3A, addition of the three proteasome-specific inhibitors, MG132, lactacystin, and ALLN, significantly increased ADRP levels after treatment for 18 h. By contrast, the other protease inhibitors were ineffective in increasing ADRP protein levels (Fig. 3A). These data indicate that ADRP can be degraded through the proteasome pathway. We also examined whether proteasomal inhibitors increase ADRP protein indirectly by elevating ADRP mRNA levels. Although addition of 5 μm MG132 for 18 h significantly increased ADRP protein levels, addition of this agent did not alter ADRP mRNA levels under the same conditions (Fig. 3B). Thus, the proteasome inhibitors elevated ADRP protein by a post-transcriptional mechanism. Proteasomal Degradation of ADRP—To examine ADRP turnover more directly, we performed pulse-chase experiments. Cells were labeled for 5 h with [35S]methionine followed by a 5-h chase in the presence of unlabeled methionine with or without 10 μm MG132 or 400 μm oleic acid. 35S-Labeled ADRP was immunoprecipitated and detected by autoradiography. More than 50% of the labeled ADRP was lost during the 5-h control chase (Fig. 4, A and B). The specific proteasome inhibitors MG132 (Fig. 4A, B), lactacystin, and ALLN (data not shown), strongly (∼85%) preserved the labeled ADRP during the chase period (Fig. 4, A and B), whereas calpeptin, leupeptin, chloroquine, and NH4Cl had no effect on ADRP degradation (data not shown). These results confirmed that degradation of ADRP was specifically mediated by the proteasomal pathway. The addition of oleic acid only modestly blunted the loss of the 35S-labe